ESGO–SIOPE guidelines for the management of adolescents and young adults with non-epithelial ovarian cancers. Issue 7 (July 2020) - Sessa, Cristiana; Schneider, Dominik T; Planchamp, François; Baust, Katja; Braicu, Elena Ioana; Concin, Nicole; Godzinski, Jan; McCluggage, W Glenn; Orbach, Daniel; Pautier, Patricia; Peccatori, Fedro A; Morice, Philippe; et al.
Summary: The European Society of Gynaecological Oncology and the European Society for Paediatric Oncology jointly developed clinically relevant and evidence-based guidelines for the management of adolescents and young adults aged 15 to 25 years with non-epithelial ovarian cancers, including malignant ovarian germ cell tumours, sex cord-stromal tumours, and small cell carcinoma of the ovary of hypercalcaemic type. The developmental process of these guidelines is based on a systematic literature review and critical appraisal process involving an international multidisciplinary developmental group consisting of experts from relevant disciplines (paediatric oncology, paediatric surgery, medical oncology, pathology, psycho-oncology, gynaecological oncology, and reproductive endocrinology). Given the specific and often complex issues involved in treating this group of patients, fertility sparing surgery and decrease of acute and long-term toxicities from treatment were important criteria for guidelines definition. Prior to publication, the guidelines were reviewed by 54 independent international practitioners in cancer care delivery.